2016
DOI: 10.3109/09537104.2016.1170112
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic thrombocytosis in gastrointestinal cancer

Abstract: It has been demonstrated recently in several solid tumors that thrombocytosis at diagnosis may correlate with tumor invasion, metastatic progression and worse outcome. Several details of the pathomechanism of the relationship of thrombocytosis and cancer have been elucidated; however, the complete process is not clearly understood. Several hypotheses have been proposed. Recently, it was suggested that in ovarian cancer elevated IL-6 production by the tumor may induce increased megakaryopoiesis via hepatic thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 58 publications
4
45
2
2
Order By: Relevance
“…A CRC-betegek jelentős többségénél emelkedik a thrombocyták száma, thrombocytosis alakul ki [12,[41][42][43], melynek hátterében több feltételezett mechanizmus állhat [15,44]. A T2DM-ről is ismert, hogy a betegség progressziója során a thrombocyták diszfunkciója alakul ki [45][46][47][48].…”
Section: Megbeszélésunclassified
See 1 more Smart Citation
“…A CRC-betegek jelentős többségénél emelkedik a thrombocyták száma, thrombocytosis alakul ki [12,[41][42][43], melynek hátterében több feltételezett mechanizmus állhat [15,44]. A T2DM-ről is ismert, hogy a betegség progressziója során a thrombocyták diszfunkciója alakul ki [45][46][47][48].…”
Section: Megbeszélésunclassified
“…A tumoros betegségekhez társuló thrombocytosis diagnózisának meghatározásához az irodalomban szá-mos eltérő thrombocyta-határértéki adat található. A leggyakrabban alkalmazott thrombocytosis-határérték a laboratóriumok által is használt normáltartomány felső határa (400 giga/l), de ismertek ettől eltérő, további határértékek is az irodalomból [15].…”
unclassified
“…Activated transcription factors (NF‐κB, STAT3, HIF1α) enhance tumor cells to produce chemokines, cytokines, prostaglandins, growth factors to recruit inflammatory cells including neutrophils, lymphocytes, macrophage and mast cells . As platelets are part of the inflammation process, paraneoplastic thrombocytosis is common in solid cancer . There were some reports about the relationship between inflammation and prognosis, including neutrophils, lymphocytes, platelets and the combinations between them, such as neutrophils‐to‐lymphocytes rate (NLR), derived NLR (dNLR), platelets‐to‐lymphocytes rate (PLR) .…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 9 11 ] Similarly, the results of a growing number of clinical studies have indicated that platelet counts are associated with overall survival (OS) and disease-free survival (DFS) in colorectal cancer, [ 8 , 12 – 14 ] but this claim remains controversial; some studies indicate that preoperative thrombocytosis is a poor predictor of survival in colorectal cancer patients, while others suggest that there is no correlation between preoperative thrombocytosis and the survival in colorectal cancer patients. [ 14 – 17 ]…”
Section: Introductionmentioning
confidence: 99%